STRATEGI KOMUNIKASI PUBLIC RELATIONS TAMAN ISMAIL MARZUKI DALAM MEMANFAATKAN INSTAGRAM UNTUK MEMPERTAHANKAN REPUTASI DI ERA DIGITAL - Novelia Simare Mare; Fauzi Syarief (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The development of information technology in the digital era requires organizations, including cultural institutions such as Taman Ismail Marzuki (TIM), to manage communication and maintain their reputation through social media, particularly Instagram. This study aims to analyze the Public Relations communication strategy implemented by Taman Ismail Marzuki in utilizing Instagram to maintain its reputation in the digital era while also increasing Generation Z's interest in visiting, following the institution's revitalization in 2022. This study employs a qualitative approach with a case study design and a constructivist paradigm. Data were collected through in-depth interviews, observation, and documentation studies, then analyzed using Cutlip and Center's Public Relations managerial approach, which consists of four stages, namely fact finding, planning, communication-action, and evaluation, complemented by a SWOT and 4P analysis of Taman Ismail Marzuki's Instagram account. The results show that Taman Ismail Marzuki uses Instagram as its main channel to build brand awareness as well as an image as an active, open, and contemporary center for art and culture. The consistency of the content produced has proven capable of shaping a positive perception, both internally and among visitors/followers, as well as encouraging direct visits, particularly among Generation Z as the main target audience. Thus, it can be concluded that Taman Ismail Marzuki's Public Relations communication strategy through Instagram has been implemented systematically and quite effectively in maintaining its reputation in the digital era, although several aspects still need to be further developed, particularly content interactivity and collaboration with creators and communities to further engage Taman Ismail Marzuki with its Generation Z audience.